ISSUES OF IMPROVING THE LEGAL FRAMEWORK OF THE PENSION SYSTEM IN THE REPUBLIC OF KAZAKHSTAN (Journal of actual problems of jurisprudence, 2026)
The article addresses the legal regulation of the pension system in the Republic of Kazakhstan.Kazakhstan is a democratic, legal, and social state, whose political course is aimed at ensuring conditions for a decent life and free development of citizens. At the same time, the pension provision of citizens involves the provision of a certain amount of state guarantees to ensure a decent life for all categories of citizens.The article examines the dynamics and state of the pension system in the Republic of Kazakhstan as one of the first states to initiate the reform of the joint pension system among the post-Soviet states. The structure of the formation of pension provision for the population was determined, and the results of the analysis of the investment activities of the Unified Accumulative Pension Fund were presented.The authors consider the concept of «pension provision» and the legal, social, and economic aspects of pension provision. Also, observing the principle of accumulation, but expanding the possibilities of pension funds and individual voluntary opportunities of citizens in terms of pension provision, it supports further measures to diversify the investment portfolio of pension funds and expand the list of financial instruments suitable for investment at the expense of pension assets to ensure sufficient profitability of pension savings. To restore confidence in the pension system, the Government proposes developing a long-term strategy and concludes that it is necessary to adopt a new program for fundamental reforms.Key words: pension system, distributive and accumulative models, pension provision, Unified Accumulative Pension Fund, Social Code.